Effect of Prior Cyclic Loading on Triaxial Compression Strength of Sliding Zone Soil of the Huangtupo Landslide - Qiong Chen; Deshan Cui; Yu Chen; Xianyu Tao; Wei Xiang (Advances in Civil Engineering)
Earthquakes or cyclic loadings cause significant changes in the strength characteristics of soil. These changes, especially for sliding zone soil, can lead to catastrophic landslides. Taking into account this characteristic, this paper investigates the effects of prior cyclic loading on the consolidated undrained triaxial compression strength of sliding zone soil with the KTL triaxial automated system. Our experimental results indicate that the prior cyclic loading has a significant effect on the strength behaviour of saturated sliding zone soil. Under different confining pressures, cycle periods, and number of cycles, the samples exhibit the characteristics of strain-hardening. Deviatoric stress under cyclic loading condition is smaller than that with monotonic loading condition under different confining pressures, cycle periods, and number of cycles. As the confining pressure and cycle period increase, the failure stress ratio decreases. The axial strain exhibits a steep rise first and then stays stable under a cycle period of 90 s, while the axial strain shows a linear increase with an increase in the number of cycles under a cycle period of 10 s under confining pressures of 100 kPa and 400 kPa, respectively. The logarithmic relation correlates well with the failure stress ratio in the cyclic loading tests, which preliminary validates the applicability of logarithmic relation for sliding zone soil influenced by prior cyclic loading, providing a theoretical basis and guidance for the further understanding of strength characteristics of sliding zone soil.